Geo-Political Checkmate in the Indian Ocean Region: 21st Century Maritime Silk Road, Energy Security and Indo-US Nexus - Imran Khan; Muhammad Imran; Hamid Iqbal (Universitas Muhammadiyah Yogyakarta, 2019)
The study intends to explore the connection between China’s energy security, 21st Century Maritime Silk Road (MSR), and its anticipated impacts on Indo-US strategic perception in the Indian Ocean region. China’s economic prosperity and industrial boom is fomenting different variables to upset the U.S. led world order. In the back drop of energy security as core national interest, Chinese leadership has exceptionally focused the maritime domain. In addition to this, for uninterrupted industrial growth, China largely relies on energy imports that have turned its attention to the strategic value of the Sea lines of communication (SLOCs). However, China’s newly emerged interests and subsequent investment in different sea ports along the oceanic supply chain of Indian Ocean is fuelling Indo-US strategic distrust in the region. The study concludes that China’s carefully craftedMaritime Silk Road (MSR) is to challenge the status quo to protect its (China) core national interests in Indian Ocean The divergence of strategic interests in Indian Ocean is heralding a new multipart strategic competition that will transform the Indian Ocean into breeding ground for naval arm race. To understand the shifting geo political realities, the researchers used the Power Transition theory.